Nanostructured tungsten carbide/carbon composites synthesized by a microwave heating method as supports of platinum catalysts for methanol oxidation - Lu, Jin Lin (2013)
In this work, a series of nanostructured tungsten carbide/carbon (WC/Cx) composites are in situ synthesized using a microwave heating method. The composites are used as platinum (Pt) catalyst supports for methanol oxidation in acid media. Their structure, composition and specific surface area are characterized by X-ray diffraction (XRD), energy dispersive spectroscopy (EDS), Raman spectroscopy, and Brunauer–Emmett–Teller (BET) measurements. Platinum catalysts supported on the WC/Cx composites are synthesized by an improved impregnation method. The electrochemical performance and stability of the catalysts are evaluated by cyclic voltammetry (CV) and chronoamperometry (CA). The Pt/WC/Cx catalysts exhibit higher activity and stability than does the Pt/VC (Pt supported on carbon black Vulcan XC-72) catalyst. The results indicate that there is a synergistic effect between Pt and the WC/Cx support, which can promote the electrocatalysis of Pt for methanol oxidation reaction (MOR).